2007
DOI: 10.1590/s0066-782x2007001500005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos níveis séricos de homocisteína em transplantados renais com e sem hipercolesterolemia

Abstract: SummaryBackground: Hyperhomocysteinemia seems to be frequent after renal transplantation. No study so far has assessed the role of homocysteine (Hcy) associated with dyslipidemia in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The articles were then classified according to their study design. Cross-sectional studies 15 - 18 and case reports were the types most frequently found, respectively in Arquivos Brasileiros de Cardiologia and Revista Brasileira de Cirurgia Cardiovascular. 19 , 20 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The articles were then classified according to their study design. Cross-sectional studies 15 - 18 and case reports were the types most frequently found, respectively in Arquivos Brasileiros de Cardiologia and Revista Brasileira de Cirurgia Cardiovascular. 19 , 20 …”
Section: Discussionmentioning
confidence: 98%
“…Cross-sectional studies [15][16][17][18] and case reports were the types most frequently found, respectively in Arquivos Brasileiros de Cardiologia and Revista Brasileira de Cirurgia Cardiovascular. 19,20 The two periodicals together published a total of five guidelines, both in regular issues and in supplements, as can be seen in Arquivos Brasileiros de Cardiologia.…”
Section: Discussionmentioning
confidence: 98%